A Broadband Optical Diode for Linearly Polarized Light Using Symmetry‐Breaking Metamaterials. Issue 19 (7th August 2017) - Kim, Minkyung; Yao, Kan; Yoon, Gwanho; Kim, Inki; Liu, Yongmin; Rho, Junsuk
Abstract : As an analog of electrical diodes, optical diodes enable asymmetric transmission or one‐way transmission of light. Here, a thin bilayer metamaterial supporting asymmetric transmission is experimentally demonstrated for linearly polarized light but not for circularly polarized light over a broad bandwidth up to 50 terahertz in the near‐infrared region. A simple and intuitive working principle based on the symmetry inherent in the metamaterial design is provided, along with full‐wave simulations that agree well with the experimental results. It is also proved that the design is extremely insensitive to spatial misalignment, which may occur during the nanofabrication process. These prominent features promise a wide range of applications, such as ultrafast optical computing, information processing, and suppressing undesired interactions of light in integrated micro‐ and nanodevices. Abstract : Optical diodes that allow unidirectional light transportation as an optical analogy of electrical diodes are in high demand. A metamaterial supporting a broad range of asymmetric transmission and its physical background is demonstrated. The asymmetric light behavior will enable a variety of photonic applications such as on‐chip optical computing and information communication.